The amazing systemic structure of Mathematics - Ramon Blanco Sanchez (Annals of Mathematics and Physics - Peertechz Publications, 2022)
Starting with the works of Ludwig von Bertalanffy, the general systems theory went from being applied to biological systems to identifying systemic structures in different natural, technological and social phenomena, even systemic structures are appreciated in different branches of science.